Predisposing and Precipitating Factors of Schizophrenic Clients with the Risk of Violent Behavior and Hallucination - Budiarto, Eka; Rahayu, Rita; Fitriani, Nurlaila (Universitas Muhammadiyah Surakarta, 2022)
The management of schizophrenia clients especially those who are at risk of violent behavior and hallucinations clients, its takes a long time. The management can be successful if it focuses on redisposing and precipitation factors. This study aimed to determine the predisposing and precipitation clients of risk factors for violent behavior and hallucinations. This research was descriptive analytic study. The sample was obtained with a total sampling of 48 respondents who met the inclusion criteria. Data were collected using a checklist of predisposing and precipitation factors and analyzed by frequency distribution. The predisposing factors found that caused schizophrenic clients to experience the risk of violent behavior and hallucinations were history of previous mental disorders (72.9%), unpleasant experiences and negative self-concept (100%) and the condition of clients who did not work (79.2%). Most of the precipitation factors found were drug withdrawal (50%), problem solving was 41.7%, and not working which reached 66.7%. Clients with schizophrenia who are at risk of violent behavior and hallucinations can be managed properly by considering the predisposition and precipitation that triggers the client to experience schizophrenia and relapse.